STANDARDIZATION IN DOCUMENTARY INSTITUTIONS IN THE MARKET ENVIRONMENT - BLIŪDŽIUVIENĖ, NIJOLĖ BLIŪDŽIUVIENĖ (Knygotyra, 2015)
Libraries, museums, and archives when providing user services generate value out of transforming information into service. Documentary institutions aim to provide more user value adhering to standards as a means for establishing innovative coordinated systems that are appropriate for provision of widely accessible services, achieving competitive supremacy, and participation in the information services market.The information infrastructure comprises entire computer and communication systems as well as information content intended for services, creators and users of information resources. Integrating standards as part of its own framework, the information infrastructure plays an important role in public welfare as a great number of social spheres become increasingly dependent on information technologies.Adoption of international and open standards by libraries, museums, and archives enables them to find solutions for intersector collaboration and makes a strong case for interoperability, semantic, and organizational compatibility which gives advantage in the market and service provision activities.Libraries, museums, and archives institutions apply specific requirements for documentation structure and content. Separately created systems may be integrated into a common system, or a single system may be established by several coordinated institutions. It requires collaborative agreements on standards’ implementation, ensuring the interoperability and continuity of systems, more economical system support and management as well as easy maintenance that meets the user’s needs.Responding to emerging technological challenges, documentary institutions establish new electronic services available to users within their own countries and worldwide and become recognized actors within the economic and social infrastructure and the market. Libraries, museums, and archives are user-oriented institutions. By implementing the newest technologies and adhering to commonly agreed standards, they have an opportunity to successfully enter the market, operate and compete there both on national and global levels providing free access to digitized cultural heritage objects.
Keywords: ...